Genome-Guided Insights into the Plant Growth Promotion Capabilities of the Physiologically Versatile Bacillus aryabhattai Strain AB211 - Bhattacharyya, Chandrima; Bakshi, Utpal; Mallick, Ivy; Mukherji, Shayantan; Bera, Biswajit; Ghosh, Abhrajyoti (Frontiers in Microbiology, 2017)
Bacillus aryabhattai AB211 is a plant growth promoting, gram positive firmicute, isolated from the rhizosphere of tea (Camellia sinensis), one of the oldest perennial crops and a major nonalcoholic beverage widely consumed all over the world. The whole genome of B. aryabhattai AB211 was sequenced, annotated and evaluated with special focus on genomic elements related to plant microbe interaction. It's genome sequence reveals the presence of a 5,403,026 bp chromosome. A total of 5226 putative protein-coding sequences, 16 rRNA, 120 tRNA, 8 ncRNAs, 58 non-protein coding genes, and 11 prophage regions were identified. Genome sequence comparisons between strain AB211 and other related environmental strains of B. aryabhattai, identified about 3558 genes conserved among all B. aryabhattai genomes analyzed. Most of the common genes involved in plant growth promotion activities were found to be present within core genes of all the genomes used for comparison, illustrating possible common plant growth promoting traits shared among all the strains of B. aryabhattai. Besides the core genes, some genes were exclusively identified in the genome of strain AB211. Functional annotation of the genes predicted in the strain AB211 revealed the presence of genes responsible for mineral phosphate solubilization, siderophores, acetoin, butanediol, exopolysaccharides, flagella biosynthesis, surface attachment/ biofilm formation, and indole acetic acid production, most of which were experimentally verified in the present study. Genome analysis and experimental evidence suggested that AB211 has robust central carbohydrate metabolism implying that this bacterium can efficiently utilize the root exudates and other organic materials as an energy source. Genes for the production of peroxidases, catalases, and superoxide dismutases, that confer resistance to oxidative stresses in plants were identified in AB211 genome. Besides these, genes for heat shock tolerance, cold shock tolerance, glycine-betaine production, and antibiotic /heavy metal resistance that enable bacteria to survive biotic/abiotic stress were also identified. Based on the genome sequence information and experimental evidence as presented in this study, strain AB211 appears to be metabolically diverse and exhibits tremendous potential as a plant growth promoting bacterium.